2023
DOI: 10.21831/cp.v42i1.53041
|View full text |Cite
|
Sign up to set email alerts
|

Misconception of reading literacy and its impacts on literacy acculturation in school

Abstract: Literacy competencies are important for students to keep abreast of the pace in the 4.0 industrial age. Misunderstanding of the concept of literacy may result in the incorrect application of literacy acculturation. This study is aimed at 1) describing teachers’ misconceptions of reading literacy and 2) describing the implementation of students’ reading literacy acculturation at school. Data were collected from teachers’ and students’ statements and activities during the literacy acculturation activities in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Misconceptions are often experienced by students, but it does not rule out the possibility that teachers also experience misconceptions. According to Härmälä-Braskén et al, (2020) and Fauzan et al, (2023) there are several studies that show that misconceptions are not only experienced by students but also teachers. Factors causing misconceptions in teachers include a low level of reasoning, lack of learning resources, limited information, lack of mastery of the field, and cumulative misconceptions experienced by teachers while still in school (Potvin & Cyr, 2017;Hala et al, 2018;Resbiantoro et al, 2022).…”
Section: Problem Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…Misconceptions are often experienced by students, but it does not rule out the possibility that teachers also experience misconceptions. According to Härmälä-Braskén et al, (2020) and Fauzan et al, (2023) there are several studies that show that misconceptions are not only experienced by students but also teachers. Factors causing misconceptions in teachers include a low level of reasoning, lack of learning resources, limited information, lack of mastery of the field, and cumulative misconceptions experienced by teachers while still in school (Potvin & Cyr, 2017;Hala et al, 2018;Resbiantoro et al, 2022).…”
Section: Problem Statementmentioning
confidence: 99%
“…Misconceptions in students can hinder the learning process and students' scientific understanding, therefore students cannot solve problems in everyday life (Halim et al, 2018;Nurjani et al 2020;Resbiantoro et al, 2022). Misconceptions can occur to anyone including teachers (Kikas, 2004;Fauzan et al, 2023). Misconceptions experienced by teachers can potentially lead to the development of similar misconceptions among students.…”
Section: Misconceptionmentioning
confidence: 99%
“…Literacy competencies are essential for students to keep pace with the demands of the Industrial Revolution 4.0 (Fauzan et al, 2023). They are a significant aspect of education that strengthens 21st-century skills, which are expected to be applied in the real world.…”
Section: Reading Literacy Assessmentmentioning
confidence: 99%
“…Another study concluded that this poor performance in reading in international assessments such as PISA is grounded on the major misconceptions of Indonesian teachers in the aspect of teaching reading. High school teachers viewed such endeavor as a shallow task which only focused on the pronunciation of words and literal meaning of texts (Fauzan et al, 2023). In contrary, Ahmed et al (2021) posited that teaching reading among students is beyond the surface level, as it must involve the complex stimulation of different life skills such as critical thinking skills, socio-emotional empathy, and cultural awareness in order to aid students to effectively understand human emotions and cultural connotations in texts, obtain information, master knowledge, utilize this information to overcome any challenges, and construct new substantial ideas.…”
Section: Introductionmentioning
confidence: 99%